Intercultural Competence and Cultural Awareness in the Foreign Language Classroom: Evolution of the Concept of Culture in a Beginner Group - Dávila-Romero, Raúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study explores didactic resources to promote intercultural reflection in the foreign language classroom. In a beginner group (A1.2 level) of German as a foreign language in a Spanish university, activities for the development of intercultural communicative competence were integrated into a previous program with communicative orientation and a strong presence of oral peer interaction. The results obtained in this quasi-experimental research report on the development of cultural awareness of the participants.